La Malnutrición Infantil en Esmeraldas: ¿un éxito relativo? Child malnutrition in Esmeraldas: a relative success? (La U Investiga, 2020)
Child malnutrition in Ecuador is a social problem. At the provincial level, Esmeraldas is the province with the lowest relative prevalence, being the least overweight in children, and among the three with the least stunting in children. The objective of this research is to examine the evolution of child malnutrition in Esmeraldas, its peculiarities, progress and challenges. The methodology is quantitative, using data from the Living Conditions Surveys 1999-2006-2014, and makes estimates with regression analysis. Among the main results is that stunting and childhood overweight have different determinants, associated with social and personal factors.
Keywords: child malnutrition; child stunting; child overweight; Esmeraldas; regression analysis